Pre-Raphaelite drawing - Cruise, Colin (Thames & Hudson, 2012)
Copiously illustrated with pre-Raphaelite drawings from public and private collections around the UK, the book features an illuminating text by the renowned art historian Colin Cruise, offering a fresh and intimate perspective on this much-loved group of artists.